Reversing Cochlear Nucleus Maladaptive Plasticity via Customized Extracochlear Stimulation: A New Approach for Tinnitus Treatment - Min Chen; Shuwen Fan; Jiabao Mao; Linhan Huang; Nafisa Tursun; Chen Zhang; Wen Li; Shufeng Li (Advanced Science)
Abstract Tinnitus, a widespread condition affecting numerous individuals worldwide, remains a significant challenge due to limited effective therapeutic interventions. Intriguingly, patients using cochlear implants (CIs) have reported significant relief from tinnitus symptoms, although the underlying mechanisms remain unclear and intracochlear implantation risks cochlear damage and hearing loss. This study demonstrates that targeted intracochlear electrical stimulation (ES) in guinea pigs with noise‐induced hearing loss reversed tinnitus‐related maladaptive plasticity in the cochlear nucleus (CN), characterized by reduced auditory innervation, increased somatosensory innervation, and diminished inhibitory neural networks. Additionally, a customized extracochlear ES delivered by a newly designed extracochlear electrode array to guinea pigs with salicylate‐induced tinnitus also reversed the aforementioned maladaptive plasticity and alleviated tinnitus without causing additional cochlear damage or hearing loss. These findings suggest that CI‐delivered ES may alleviate tinnitus by reversing maladaptive CN plasticity. Additionally, the extracochlear ES strategy offers a promising tinnitus treatment with minimal risk to hearing.